After peritoneal dialysis discontinuation: When will we remove peritoneal dialysis catheter?. Issue 1 (May 2019) - Kasuga, Hirotake
Most of the peritoneal dialysis patients stop their peritoneal dialysis therapy and transfer to hemodialysis or kidney transplantation. In Japan, most end-stage kidney disease patients select hemodialysis after peritoneal dialysis discontinuation. Peritoneal dialysis catheter will be removed after stopping peritoneal dialysis. If peritoneal dialysis patients suffer from refractory peritonitis or severe tunnel infection, we remove the peritoneal dialysis catheter immediately. However, the causes of peritoneal dialysis discontinuation are ultrafiltration failure or peritoneal membrane dysfunction, and we have to consider the timing of peritoneal dialysis catheter removal. Encapsulating peritoneal sclerosis is the most important adverse event of peritoneal dialysis. And encapsulating peritoneal sclerosis often develops after stopping peritoneal dialysis. Risk factors associated with encapsulating peritoneal sclerosis are high peritoneal equilibration test values, longer peritoneal dialysis period, frequent peritonitis, and so on. There is no evidence to prevent encapsulating peritoneal sclerosis completely. Therefore, we can preserve the peritoneal dialysis catheter and assess the changes of peritoneal function after peritoneal dialysis discontinuation, if patient is suspected to have high risk of encapsulating peritoneal sclerosis.